A 5‐ to 6‐year radiological evaluation of titanium plasma sprayed/sandblasted and acid‐etched implants: results from private practice. Issue 2 (29th January 2013) - Dam, Hamasat Gheddaf; Najm, Semaan Abi; Nurdin, Nathalie; Bischof, Mark; Finkelman, Matthew; Nedir, Rabah
Abstract Objectives This study aimed to determine bone level changes after 5–6 years of follow‐up for a large group of one‐stage dental implants consecutively placed in private practice. Potential confounding factors influencing crestal bone loss (CBL) were also assessed. Materials and methods A total of 378 transmucosal Straumann® implants in 174 patients were examined radiographically. Half of the study population (189 implants) had a titanium plasma sprayed (TPS) surface, and the other half (189 implants) were sandblasted and acid‐etched (SLA). Mean CBL was measured from 5 to 6 years post‐operative radiographs on the basis of known implant landmarks. Correlations of increased CBL with various independent variables were also investigated. Statistical analyses were performed using generalized estimating equations. Results Radiographic measurements showed a CBL ≤ 1.5 mm for 65% of studied implants. A CBL > 1.5 mm was found for 28% of implants, while 7% of implants had a CBL ≥ 3 mm. Three factors significantly influenced CBL (P < 0.05): implant surface texture (TPS > SLA), smoking status (smokers > non‐smokers), and implant location (anterior > posterior). Conclusions CBL was ≤1.5 mm after 5–6 years for the majority of followed implants. For implants with a CBL > 1.5 mm, statistically significant correlations were found for TPS surface type, anterior jaw locations, and smoking. Implant length did not influence CBL.